Research and Implement Artificial Intelligence (AI ) to Create a Microservice-Based E-commerce System - Le, Vu Ngoc Huy (Vietnam - Korea University of Information and Communication Technology, 2024)
Graduation thesis of Information Technology; 2019 - 2024.